Close Association of Carbonic Anhydrase (CA2a and CA15a), Na+/H+ Exchanger (Nhe3b), and Ammonia Transporter Rhcg1 in Zebrafish Ionocytes Responsible for Na+ Uptake - Ito, Yusuke; Kobayashi, Sayako; Nakamura, Nobuhiro; Esaki, Masahiro; Miyagi, Hisako; Hoshijima, Kazuyuki; Hirose, Shigehisa (Frontiers in Physiology, 2013)
Freshwater fishes actively absorb salt from their environment to tolerate low salinities. We previously reported that vacuolar-type H+-ATPase/mitochondrion-rich cells (H-MRCs) on the skin epithelium of zebrafish larvae (Danio rerio) are primary sites for Na+ uptake. In this study, in an attempt to clarify the mechanism for the Na+ uptake, we performed a systematic analysis of gene expression patterns of zebrafish carbonic anhydrase (CA) isoforms and found that, of 12 CA isoforms, CA2a and CA15a are highly expressed in H-MRCs at larval stages. The ca2a and ca15a mRNA expression were salinity-dependent; they were up-regulated in 0.03 mM Na+ water whereas ca15a but not ca2a was down-regulated in 70 mM Na+ water. Immunohistochemistry demonstrated cytoplasmic distribution of CA2a and apical membrane localization of CA15a. Furthermore, cell-surface immunofluorescence staining revealed external surface localization of CA15a. Depletion of either CA2a or CA15a expression by Morphorino antisense oligonucleotides resulted in a significant decrease in Na+ accumulation in H-MRCs. An in situ proximity ligation assay demonstrated a very close association of CA2a, CA15a, Na+/H+ exchanger 3b (Nhe3b), and Rhcg1 ammonia transporter in H-MRC. Our findings suggest that CA2a, CA15a, and Rhcg1 play a key role in Na+ uptake under freshwater conditions by forming a transport metabolon with Nhe3b.